Antibacterial Activity of some Fresh Water Algae - A.M. Chavan2, S.M. Kamble1* and (Journal of Experimental Sciences, 2010)
<div style="border-right: medium none; padding-right: 0in; border-top: windowtext 1pt solid; padding-left: 0in; background: white; padding-bottom: 0in; border-left: medium none; padding-top: 1pt; border-bottom: medium none; mso-element: para-border-div; mso-border-top-alt: solid windowtext .5pt;"> Present deals with the study of antibacterial activity of some fresh water algae against some bacteria. It was found that some fresh water algae showed antibacterial activity. -------------------------------------------------------------------------------------------------------- 1Department of Botany, Sangmeshwar College, Solaphur (M.S.), India; 2Department of Botany Dr. Babasaheb Ambedkar Marathwada University, Aurangabad 431004 (M.S.), India * Corresponding Author, Email: suhaskamble@rediffmail.com Please Cite This Article As: S.M. Kamble and A.M. Chavan. 2010. Antibacterial Activity of some Fresh Water Algae.J. Exp. Sci. 1(2): 05-06.